Harper Handles Big Feelings : Lessons for littles on Anger, Worry, Frustration, and other emotions - Jannuzzi, Jayme; Bajet, John John ([Place of publication not identified] : Z Kids, 2025)
Harper Handles Big Feelings is a sweet and relatable story about the power of self-regulation. Jayme guides the reader through the very real and complex emotions that children experience throughout the day. The adorable Harper empowers young learners to identify and connect to their own feelings and use the book's age-appropriate calm down rhyme to support themselves during times of big emotions.
new kids book 2025 summer.
Keywords: Emotions and Feelings; Health and daily living; Mental health; Inspirational and personal growth